Preparation method and application of metal-doped activated carbon microspheres
Metal-doped activated carbon microspheres with embedded metal oxides and increased hydrophilicity address the limitations of carbon materials as catalyst carriers, achieving high efficiency in catalytic hydrogenation reactions.
Patent Information
- Application Number
- CN202211688488.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2042-12-27
AI Technical Summary
Existing carbon materials lack sufficient Lewis acid centers and hydrophilicity, limiting their effectiveness as catalyst carriers, particularly in catalytic hydrogenation reactions.
A method involving metal-doped activated carbon microspheres is developed, where metal oxides are embedded into a carbon material skeleton through a block-carbonization-activation process, followed by water vapor activation to increase hydrophilicity and provide sufficient Lewis acid centers, allowing for the loading of active metals as auxiliary components.
The method results in catalysts with enhanced activity and selectivity, achieving 100% nitrobenzene conversion and 100% aniline selectivity in hydrogenation reactions, expanding the application scope of carbon materials.
Smart Images

Figure CN115945201B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method and application of metal-doped activated carbon microspheres, belonging to the technical field of carbon material synthesis and application. Background Art
[0002] Carbon materials are a new type of material with a wide range of applications, playing an important role in the fields of gas capture and separation, organic adsorption, catalysis, etc. Carbon materials can be divided into a series of types with different structures and properties, such as activated carbon, carbon nanotubes, carbon fibers, graphene, and ethylene. They are mostly made by carbonization and activation of organic matter such as polymers and biomass, or by dehydrogenation of gaseous carbon sources such as methane and acetylene. With the rapid development of materials science, carbon materials have also developed from pure carbon to heteroatom-carbon composite materials, such as nitrogen-carbon, boron-carbon, metal-carbon composites, etc. Due to the incorporation of heteroatoms, carbon materials also have special properties such as Lewis acidity and alkalinity, conductivity, etc., which can be more widely used in a variety of occasions requiring special performance materials. In particular, composite carbon materials derived from porous organic polymers (POPs), metal organic frameworks (MOFs), covalent organic frameworks (COFs) and other materials have received widespread attention due to their excellent physical and chemical stability and multi-level pore structure characteristics, and their applications in adsorption separation, organic selective removal and other fields are becoming more and more significant.
[0003] To date, about 90% of chemical reactions require catalysts to be realized. Carbon materials as a catalyst carrier also have many applications. For example, activated carbon-supported cobalt-based catalysts are used in the conversion of syngas to produce oil products and fine chemicals such as high-carbon alcohols, and nanodiamond-supported palladium-based catalysts are used in the selective hydrogenation of cinnamaldehyde with very good activity and selectivity. Metal-carbon hybrid compounds also show good catalytic effects and are widely used in the fields of syngas conversion and catalytic hydrogenation of fine chemicals, and a large number of articles have been published. In particular, carbon materials, as a new type of environmentally friendly material, can remove carbon elements through pyrolysis, easily recover metals, and avoid the steps of acid dissolution and precipitation of other carriers that produce a large amount of three wastes, which has great environmental significance and value. Therefore, the development of carbon-supported catalysts has been an area of focus in the field of catalysis in recent years. Moreover, with the deepening of the understanding of the relationship between the structure and performance of carbon materials, the design of hybrid carbon material carriers with composite structures and adjustable acidity and alkalinity will help expand the application range of carbon materials and have more significant significance and value. Summary of the invention
[0004] According to one aspect of the present application, a method for preparing metal-doped activated carbon microspheres is provided, wherein a metal block-carbonization-activation method is used to embed metal oxides into a carbon material skeleton to form a metal-carbon composite material with high metal dispersion, thereby providing sufficient Lewis acid centers for the carbon carrier. The surface hydrophilicity is then increased by water vapor activation, so that the active metal can be loaded by impregnation, ion exchange or spraying, and the original metal on the carbon carrier becomes an auxiliary component, which can effectively adjust the electronic properties of the active metal and improve the activity and selectivity of the catalyst.
[0005] This application adopts the following technical solutions:
[0006] A method for preparing metal-doped activated carbon microspheres comprises the following steps:
[0007] S1, soaking the macroporous polymer particles in an organic solution containing a metal salt, and drying to obtain modified polymer particles blocked with metal salts;
[0008] The average pore size of the macropores in the macroporous polymer particles is 80 to 200 nm, and the pore volume of the macropores is 0.18 to 0.5 cc / g;
[0009] S2. The modified polymer particles obtained in step S1 are calcined and carbonized under an inert atmosphere, and then activated with water vapor to obtain metal-doped activated carbon microspheres with a multi-level structure.
[0010] Optionally, in step S1, the material of the macroporous polymer particles is selected from at least one of ion exchange resin, phenolic resin, PVC, CPVC, CPE, and PVDC.
[0011] In addition to C and H elements, polymer particles with a macroporous loose structure must also contain heteroatoms such as halogens, N and O.
[0012] Optionally, in step S1, the organic solution is selected from at least one of ethanol, acetylacetone, tetrahydrofuran, N-dimethylformamide, acetone, and toluene.
[0013] The above organic solution plays a role of swelling, so that the metal ions can be embedded in the polymer chain segments. At the same time, the metal ions can also be embedded in the polymer chain segments through ion exchange.
[0014] Optionally, in step S1, the metal salt is selected from at least one of soluble salts of Fe, La, Ce, Cr, Mo, W, Zn, and Mn.
[0015] Optionally, the soluble salt is selected from at least one of nitrate, chloride, sulfate, ammonium salt and acetate.
[0016] Optionally, in step S1, the particle size of the macroporous polymer particles is 0.1 to 1 mm.
[0017] Optionally, in step S1, the weight concentration of the metal salt in the organic solution is 0.2-1 g / ml.
[0018] Optionally, in step S1, the weight concentration of the metal salt in the organic solution is selected from any value of 0.2g / ml, 0.3g / ml, 0.4g / ml, 0.5g / ml, 0.6g / ml, 0.7g / ml, 0.8g / ml, 1g / ml, or any range between the two.
[0019] Optionally, in step S1, the soaking time is 5 to 48 hours.
[0020] Optionally, in step S1, the soaking time is selected from any value of 5h, 20h, 24h, 30h, 40h, 48h, or any range therebetween.
[0021] The metal elements contained in the metal-doped activated carbon microspheres act as additives and can interact with the loaded active metals to obtain a catalyst with good activity and selectivity.
[0022] Optionally, the loading amount of the metal salt in the metal salt-block modified polymer particles is 0.5 to 5 wt %.
[0023] Optionally, in step S2, the conditions for the roasting and carbonization are: heating to 500-900° C. and keeping warm for 6-16 hours.
[0024] Optionally, in step S2, the temperature of the roasting and carbonization is selected from any value of 500°C, 600°C, 700°C, 800°C, 900°C, or any range therebetween.
[0025] Optionally, in step S2, the holding time for the roasting and carbonization is selected from any value among 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, or any range between them.
[0026] Optionally, the conditions for the water vapor activation treatment are: adding water vapor with a concentration of 1 to 5% in an inert atmosphere, heating to 700 to 900° C. and keeping the temperature for 4 to 20 hours.
[0027] Optionally, the temperature of the steam activation treatment is selected from any value of 700° C., 750° C., 800° C., 850° C., 900° C., or any range therebetween.
[0028] Optionally, in step S2, the inert atmosphere is selected from at least one of nitrogen, argon and helium.
[0029] According to another aspect of the present application, there is provided a metal-doped activated carbon microsphere prepared by the above preparation method, wherein the metal is uniformly embedded in the skeleton of the activated carbon in the form of oxide.
[0030] Optionally, the metal-doped activated carbon microspheres contain macropores and mesopores;
[0031] The average pore size of the macropores is 100-200 nm, the pore volume of the macropores is 0.2-0.5 cc / g, the average pore size of the mesopores is 20-40 nm, and the pore volume of the mesopores is 0.2-0.7 cc / g.
[0032] According to another aspect of the present application, there is provided a use of the metal-doped activated carbon microspheres prepared by the above preparation method, or at least one of the above metal-doped activated carbon microspheres as a catalyst carrier.
[0033] Optionally, the metal-doped activated carbon microspheres are used as catalyst supports for catalysts in the catalytic hydrogenation reaction of nitrobenzene.
[0034] Optionally, the catalyst is obtained by loading an active metal on the catalyst carrier;
[0035] The active metal is selected from at least one of Pd, Pt, Ru, Co, Ni and Cu.
[0036] In this application, unless otherwise specified, the data range given is selected from any value in the range and includes the endpoint value of the range.
[0037] The beneficial effects of this application include:
[0038] The present application provides a method for preparing metal-doped activated carbon microspheres, which use polymer particles with a macroporous structure as raw materials, adopt a swelling-metal embedding method to embed metal ions into polymer segments, and then undergo a calcination carbonization treatment to obtain metal-doped activated carbon microspheres with a mesoporous-macroporous multi-level structure, providing sufficient Lewis acid centers for carbon carriers. The microspheres are activated by a water vapor activation method to obtain metal-doped activated carbon microspheres with good hydrophilicity, which have special effects as catalyst carriers. In the application of catalyst carriers, active metals can be loaded by impregnation, ion exchange or spraying, and the original metal on the carbon carrier becomes an auxiliary component, which can effectively adjust the electronic properties of the active metal, improve the activity and selectivity of the catalyst, and achieve a nitrobenzene conversion rate of 100% and an aniline selectivity of 100% in a hydrogenation model reaction with nitrobenzene as a substrate and ethanol as a solvent at a nitrobenzene concentration of 10%. The hybrid carbon material carrier with a composite structure and adjustable acidity and alkalinity obtained by the preparation method of metal-doped activated carbon microspheres provided in the present application provides a new solution for expanding the application scope of carbon materials, which has more significant significance and value. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the metal-doped activated carbon microspheres of Example 1 in this application.
[0040] Figure 2 This is a photo of the metal-doped activated carbon microspheres of Example 2 in this application.
[0041] Figure 3 This is the mesopore distribution diagram of the metal-doped activated carbon microspheres of Example 1 in this application.
[0042] Figure 4 This is the mesopore distribution diagram of the metal-doped activated carbon microspheres of Example 2 in this application.
[0043] Figure 5 This is a cross-sectional SEM image and element distribution diagram of the metal-doped activated carbon microspheres in Example 1 of the present application. DETAILED DESCRIPTION
[0044] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0045] Unless otherwise specified, the raw materials and catalysts in the examples of this application were purchased through commercial channels.
[0046] Example 1
[0047] 5 grams of dried PVC particles (brand SG-5, average particle size 150μm) were soaked in 10ml of 0.5g / ml iron nitrate-ethanol solution for 24h, filtered and dried, transferred to a tube furnace, and calcined at 600℃ for 8h under nitrogen to obtain 2.1 grams of Fe-doped activated carbon microspheres. The Fe content was 4.7wt% as measured by ICP, and the average particle size of the activated carbon microspheres was 120μm as measured by Malvern particle size analyzer. The activated carbon microspheres were activated at 800℃ for 10h in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The scanning electron microscope is shown in the attached figure. Figure 1 The cross-sectional SEM images and element distribution are shown in the attached Figure 5 As shown in the figure, it indicates that the Fe element is successfully embedded in the polymer. The average pore size of the macropores of the carrier is 150nm and the pore volume is 0.8cc / g, as shown in the attached figure. Figure 3 As shown, the average pore diameter of the carrier measured by the BJH method is 18 nm, and the pore volume is 0.3 cc / g.
[0048] The carrier was impregnated with an equal volume of 2.3 ml of palladium chloride solution containing 0.9 g / 100 ml of Pd, dried at 80°C, and reduced with hydrogen at 300°C for 8 h to obtain a 1Pd / Fe-AC catalyst. The catalyst was subjected to a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10% at 120°C, 2 MPa, and a liquid space velocity of 2 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 95%.
[0049] Example 2
[0050] 5 grams of dried ion exchange resin (model D-101) were soaked in 10 ml of 0.3 g / ml lanthanum nitrate-ethanol-tetrahydrofuran solution for 30 hours, filtered and dried, transferred to a tube furnace, and calcined at 600°C for 8 hours under nitrogen conditions to obtain 3.2 grams of La-doped activated carbon microspheres. The La content was measured by ICP to be 1.2 wt%, and the average particle size of the activated carbon microspheres was measured by sieving method to be about 0.4 mm. The activated carbon microspheres were activated at 800°C for 10 hours in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The electron microscope image is similar to that of Example 1. The actual object is shown in the attached figure. Figure 2 As shown in the figure, the average pore size of the macropores of the carrier is 300nm and the pore volume is 0.9cc / g. Figure 4 As shown, the average pore diameter of the carrier measured by the BJH method is 30 nm, and the pore volume is 0.3 cc / g.
[0051] The carrier was impregnated with an equal volume of 3.9 ml of chloroplatinic acid solution containing 1.6 g / 100 ml of Pt, dried at 80°C, and reduced with hydrogen at 300°C for 8 h to obtain a 2Pt / La-AC catalyst. The catalyst was subjected to a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10% at 90°C, 2 MPa, and a liquid space velocity of 2 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 98%.
[0052] Example 3
[0053] 5 grams of dried phenolic resin beads, with a particle size of about 1mm, were soaked in 10ml of 0.3g / ml chromium nitrate-NN dimethylformamide solution for 20h, filtered and dried, transferred to a tube furnace, and calcined at 700℃ for 8h under nitrogen conditions to obtain 4 grams of Cr-doped activated carbon microspheres. The La content was measured by ICP to be 1.2wt%, and the average particle size of the activated carbon microspheres was measured by sieving method to be about 0.8μm. The activated carbon microspheres were activated at 800℃ for 10h in nitrogen with a water vapor content of 4% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 100nm and the pore volume was 0.3cc / g as measured by mercury intrusion. The average pore size of the mesopores of the carrier was 35nm and the pore volume was 0.6cc / g as measured by BJH method.
[0054] The carrier was impregnated with an equal volume of 3.6 ml of a ruthenium chloride solution containing 3.3 g / 100 ml of Ru, dried at 80°C, calcined at 300°C for 6 h under nitrogen conditions, and reduced with hydrogen at 350°C for 8 h to obtain a 3Ru / Cr-AC catalyst. The catalyst was subjected to a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and a nitrobenzene concentration of 10% at 130°C, 2 MPa, and a liquid space velocity of 2 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 94%.
[0055] Example 4
[0056] 5 grams of dried CPVC resin beads, with a particle size of about 150μm, were soaked in 10ml of 0.8g / ml ammonium tetramolybdate-ammonia-ethanol solution for 30h, filtered and dried, transferred to a tubular furnace, and calcined at 700℃ for 8h under nitrogen conditions to obtain 2 grams of Mo-doped activated carbon microspheres. The Mo element content was measured by ICP to be 2.4wt%, and the average particle size of the activated carbon microspheres was measured by Malvern particle size analyzer to be about 120μm. The activated carbon microspheres were activated at 800℃ for 6h in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 170nm and the pore volume was 0.6cc / g as measured by mercury intrusion. The average pore size of the mesopores of the carrier was 30nm and the pore volume was 0.4cc / g as measured by BJH method.
[0057] The carrier was impregnated with an equal volume of 2 ml nickel nitrate solution containing 20 g / 100 ml of Ni, dried at 80 ° C, calcined at 600 ° C for 6 h under nitrogen conditions, and reduced with hydrogen at 430 ° C for 8 h to obtain a 20Ni / Mo-AC catalyst. The catalyst was used in a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10%, at 60 ° C, 2 MPa, and a liquid space velocity of 2 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 90%.
[0058] Example 5
[0059] 5 grams of dried PVDC resin beads, with a particle size of about 150μm, were soaked in 10ml of 0.8g / ml manganese acetate-ethanol solution for 40h, filtered and dried, transferred to a tubular furnace, and calcined at 700℃ for 8h under nitrogen conditions to obtain 2 grams of Mn-doped activated carbon microspheres. The Mn element content was measured by ICP to be 2.8wt%, and the average particle size of the activated carbon microspheres was measured by Malvern particle size analyzer to be about 120μm. The activated carbon microspheres were activated at 800℃ for 6h in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 170nm and the pore volume was 0.6cc / g as measured by mercury intrusion. The average pore size of the mesopores of the carrier was 30nm and the pore volume was 0.4cc / g as measured by BJH method.
[0060] The carrier was impregnated with an equal volume of 2 ml nickel nitrate solution containing 30 g / 100 ml of Cu, dried at 80°C, calcined at 300°C for 6 h under nitrogen conditions, and reduced with hydrogen at 230°C for 8 h to obtain a 30Cu / Mn-AC catalyst. The catalyst was used in a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10%, at 140°C, 2 MPa, and a liquid space velocity of 2 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 97%.
[0061] Example 6
[0062] 5 grams of dried ion exchange resin (model D-301) were soaked in 10 ml of 0.7 g / ml zinc nitrate-ethanol-acetylacetone solution for 48 hours, filtered and dried, transferred to a tube furnace, and calcined at 600 ° C for 8 hours under nitrogen conditions to obtain 3.2 grams of Zn-doped activated carbon microspheres. The Zn content was 4.5 wt% as measured by ICP, and the average particle size of the activated carbon microspheres was about 0.4 mm as measured by sieving method. The activated carbon microspheres were activated at 800 ° C for 10 hours in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 310 nm and the pore volume was 0.9 cc / g as measured by mercury intrusion, and the average pore size of the mesopores of the carrier was 33 nm and the pore volume was 0.3 cc / g as measured by BJH method.
[0063] The carrier was impregnated with an equal volume of 3.9 ml of a copper nitrate solution containing 25 g / 100 ml of Cu, dried at 80°C, calcined at 300°C in nitrogen for 10 h, and reduced at 230°C in hydrogen for 8 h to obtain a 30Cu / Zn-AC catalyst. The catalyst was subjected to a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10% at 80°C, 2 MPa, and a liquid space velocity of 2 h. -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 98%.
[0064] Example 7
[0065] 5 grams of dried ion exchange resin (model D-201) were soaked in 10 ml of 0.4 g / ml ammonium tungstate-ammonia-ethanol-tetrahydrofuran solution for 40 hours, filtered and dried, transferred to a tube furnace, and calcined at 600 ° C for 8 hours under nitrogen conditions to obtain 3.3 grams of W-doped activated carbon microspheres. The W content was measured by ICP to be 2.5wt%, and the average particle size of the activated carbon microspheres was about 0.4mm by sieving method. The activated carbon microspheres were activated at 800 ° C for 10 hours in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 350nm and the pore volume was 0.9cc / g by mercury intrusion method. The average pore size of the mesopores of the carrier was 40nm and the pore volume was 0.2cc / g by BJH method.
[0066] The carrier was impregnated with an equal volume of 3.6 ml of nickel nitrate solution containing 18 g / 100 ml of Ni, dried at 80°C, calcined at 600°C in nitrogen for 10 h, and reduced at 430°C in hydrogen for 8 h to obtain a 20Ni / W-AC catalyst. The catalyst was used in a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10% at 60°C, 2 MPa, and a liquid space velocity of 4 h -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 99%.
[0067] Example 8
[0068] 5 grams of dried ion exchange resin (model D-201) were soaked in 10 ml of 0.4 g / ml cerium nitrate-ethanol-acetone solution for 40 hours, filtered and dried, transferred to a tube furnace, and calcined at 600 ° C for 8 hours under nitrogen conditions to obtain 3.3 grams of Ce-doped activated carbon microspheres. The Ce element content was 3wt% measured by ICP, and the average particle size of the activated carbon microspheres was about 0.4mm measured by sieving method. The activated carbon microspheres were activated at 800 ° C for 10 hours in nitrogen with a water vapor content of 3% to obtain a hydrophilic activated carbon carrier. The average pore size of the macropores of the carrier was 350nm and the pore volume was 0.9cc / g measured by mercury intrusion, and the average pore size of the mesopores of the carrier was 40nm and the pore volume was 0.2cc / g measured by BJH method.
[0069] The carrier was impregnated with an equal volume of 3.6 ml of a copper nitrate solution containing 27 g / 100 ml of Cu, dried at 80°C, calcined at 300°C in nitrogen for 10 h, and reduced at 230°C in hydrogen for 8 h to obtain a 30Cu / Ce-AC catalyst. The catalyst was subjected to a hydrogenation model reaction with nitrobenzene as substrate, ethanol as solvent, and nitrobenzene concentration of 10% at 80°C, 2 MPa, and a liquid space velocity of 4 h. -1 Under the conditions that the molar ratio of hydrogen to nitrobenzene is 100, the nitrobenzene conversion rate is 100% and the aniline selectivity is 100%.
[0070] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. Application of metal-doped activated carbon microspheres as catalyst carriers, characterized in that: The metal-doped activated carbon microspheres are used as catalyst carriers of catalysts in the catalytic hydrogenation reaction of nitrobenzene; The catalyst is obtained by loading active metal on the catalyst carrier; The active metal is selected from Cu; The metal-doped activated carbon microspheres are prepared by a method comprising the following steps: S1, soaking the macroporous polymer particles in an organic solution containing a metal salt, and drying to obtain modified polymer particles blocked with the metal salt; The average pore size of the macropores in the macroporous polymer particles is 80 to 200 nm, and the pore volume of the macropores is 0.18 to 0.5 cc / g; In the step S1, the metal salt is selected from a soluble salt of Ce; S2, calcining and carbonizing the modified polymer particles obtained in step S1 under an inert atmosphere, and then subjecting the particles to water vapor activation treatment to obtain metal-doped activated carbon microspheres with a multi-level structure; The metal is uniformly embedded in the framework of the activated carbon in the form of oxides.
2. The use according to claim 1, characterized in that: In the step S1, the material of the macroporous polymer particles is selected from at least one of ion exchange resin, phenolic resin, PVC, CPVC, CPE, and PVDC.
3. The use according to claim 1, characterized in that: In the step S1, the organic solution is selected from at least one of ethanol, acetylacetone, tetrahydrofuran, N-dimethylformamide, acetone, and toluene.
4. The use according to claim 1, characterized in that: In the step S1, the particle size of the macroporous polymer particles is 0.1-1 mm.
5. The use according to claim 1, characterized in that: In the step S1, the soaking time is 5 to 48 hours.
6. The use according to claim 1, characterized in that: The loading amount of the metal salt in the modified polymer particles having metal salt blocks is 0.5 to 5 wt %.
7. The use according to claim 1, characterized in that: In step S2, the conditions for the roasting and carbonization are: heating to 500-900° C. and keeping the temperature for 6-16 hours.
8. The use according to claim 1, characterized in that: The conditions for the water vapor activation treatment are: adding water vapor with a concentration of 1 to 5% in an inert atmosphere, heating to 700 to 900° C. and keeping the temperature for 4 to 20 hours.
9. The use according to claim 1, characterized in that: In step S2, the inert atmosphere is selected from at least one of nitrogen, argon and helium.
10. The use according to claim 1, characterized in that: The metal-doped activated carbon microspheres contain macropores and mesopores; The average pore size of the macropores is 100-200 nm, the pore volume of the macropores is 0.2-0.5 cc / g, the average pore size of the mesopores is 20-40 nm, and the pore volume of the mesopores is 0.2-0.7 cc / g.
Citation Information
Patent Citations
Spherical activated carbon loaded with metal oxide as well as preparation method and use thereof
CN108946723A
Method for in-situ one-pot preparation of Pt / Fe3O4 / C-N catalyst and application
CN111545240A
